O saber escolar como parte das formas mais desenvolvidas de saber: a questão cultural na Educação Matemática - Giardinetto, José Roberto Boettger [UNESP] (My University, 2012)
This article considers the scholastic knowledge as the expression of the most developed forms of knowledge in face of the actual development stage of the mathematics. Thus, it supports that the relation between the scholastic mathematics and the mathematics produced in different social contexts, comprises a relation between the most developed (scholastic knowledge) facing the least developed (knowledge acquired from diverse social contexts). For this reason, this work comprises some specificities of the socialhistorical development of the mathematics and the implications decurrent from this, in relation to the cultural aspect for teaching mathematics.

Este artigo parte da tese de que o saber escolar é a expressão de parte das formas mais desenvolvidas de saber atingido no atual momento de desenvolvimento da história social humana. Neste sentido, defende que a relação entre a matemática escolar e a matemática produzida em contextos sociais diversos é uma relação entre o mais desenvolvido (o saber escolar) frente ao menos desenvolvido (o saber produzido em contextos sociais diversos). Neste sentido, o trabalho tece considerações sobre especificidades do desenvolvimento histórico-social da matemática à luz dessa lógica processual e as implicações daí decorrentes quanto à questão cultural.
Scholastic knowledge as part of the most developed forms of knowledge: the cultural question for teaching mathematics
Keywords: Multiculturalism; Mathematics education; Historical-critical pedagogy; Multiculturalismo; Educação matemática; Pedagogia histórico-crítica